TECHNOLOGY-SUPPORTED PEER FEEDBACK: A LITERATURE REVIEW - Tina Priyantin (Journal of English Teaching and Linguistics Studies (JET Li), 2021)
The technology advance in language learning has become a trend in research including the implementation of peer feedback. This study aims to explore the development of technology-supported peer feedback by reviewing 10 studies published between 2016 and 2020. The results found that all studies implemented peer feedback in higher education. Regarding the tools and system, most studies conducted asynchronous learning mode in giving and receiving feedback and the use of social media reached the highest percentage. Across most studies, individual peer feedback was adopted, but anonymity was not clearly mentioned. One-round feedback was mostly implemented and there were less follow-up revised tasks. Furthermore, most studies assigned students to give corrective and structured feedback. Of all studies, using technology in peer-feedback activities could give more opportunities for students to get engaged and motivated, but not significantly improve the students’ performance, language and proficiency skills. For future research, it is suggested that researchers develop how to integrate effective technology tools into peer feedback in terms of building self-regulated learning as well as reaching learning values.